2020
DOI: 10.1007/s40858-020-00340-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and copper resistance of Xanthomonas affecting citrus

Abstract: Since citrus canker was first described in the early 1900's, four major types and three species of pathogenic xanthomonads associated to citrus were identified based on the characteristic symptoms and host range. Type A, caused by X. citri subsp. citri, develops typical raised cankered lesions and is pathogenic on most commercial citrus species and cultivars. Types B and C are caused by X. citri pv. aurantifolii which elicits canker lesions. Besides the typical type A, the more aggressive and most widely sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 88 publications
(151 reference statements)
0
24
0
Order By: Relevance
“…Within Xanthomonas strains, detection of copLAB genes indicated copper resistance (Behlau, Gochez & Jones, 2020). Previous studies showed that in culture medium, copLAB genes regulate copper accumulation through copper-binding proteins generation.…”
Section: Discussionmentioning
confidence: 99%
“…Within Xanthomonas strains, detection of copLAB genes indicated copper resistance (Behlau, Gochez & Jones, 2020). Previous studies showed that in culture medium, copLAB genes regulate copper accumulation through copper-binding proteins generation.…”
Section: Discussionmentioning
confidence: 99%
“…Most commercial sweet orange cultivars are moderately to highly susceptible to citrus canker ( de Carvalho et al, 2015 ; Mei et al, 2020 ). Currently, copper-based chemicals are the main compounds used to control citrus canker; however, their excessive use leads to environmental issues, plant stress, and bacterial resistance ( Lamichhane et al, 2018 ; Behlau et al, 2020 ; Heydarpanah et al, 2020 ). To overcome these problems, biotechnology-based approaches have shown potential to increase plant resistance against citrus canker in a sustainable way ( Caserta et al, 2020 ; Salonia et al, 2020 ; Soares et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous application of copper generates selective pressure, stimulating the emergence of resistant bacterial strains (Areas et al 2018), which may make this agrochemical inefficient in the near future. For instance, resistance to copper has already emerged in X. citri (Canteros 1999;Behlau et al 2011;Behlau et al 2020).…”
Section: Introductionmentioning
confidence: 99%